Laparoscopic Plasty for Reconstruction of Symptomatic Horseshoe Kidney - Zhang, Qi; Liu, Feng; Qi, Xiaolong; Zhang, Yuelong; He, Xiang; Zhang, Dahong (Urology Journal, 2014)
Purpose: To report our experience of transperitoneal laparoscopic plasty for reconstruction in patients with horseshoe kidney. Materials and Methods: We retrospectively analyzed 12 patients with the symptomatic horseshoe kidney who presented to our institution from March 2005 to July 2008 and underwent laparoscopic reconstruction for horseshoe kidney. Computed tomography angiography was performed prior to surgery for evaluation of the anatomic variations, since preoperative knowledge is necessary for achieving reliable vascular control. Five patients had renal stones which were extracted during surgery. All laparoscopic operations were performed by the same urologist. Results: All procedures were completed successfully and no one needed for conversion to open surgery. Mean operative time was 150 min and no major complications were observed. The average follow-up time was 28.7 months. All patients had good renal function and improved drainage with successful reconstruction. Conclusion: Laparoscopic reconstruction has since been demonstrated to be an attractive alternative in the management of the horseshoe kidney. It provides a feasible and effective alternative to conventional management.